ANALISIS MISKONSEPSI MENGGUNAKAN METODE CERTAINTY OF RESPONSE INDEX (CRI) PADA MATERI SISTEM SARAF KELAS XII MIA SMA NEGERI 3 TARAKAN - Tio Vani Simorangkir; Ibrahim Ibrahim; Zulfadli Zulfadli (Biopedagogia, 2020)
The purpose of this study was to determine the misconceptions experienced by students of class XII MIA SMA Ngeri 3 Tarakan. This research is a qualitative descriptive study that seeks to describe the conditions as they are of a subject descriptively. In this study, the researcher gave the test in the form of multiple-choice with open reasons accompanied by the Certainty of Response Index (CRI) column to students to provide an overview of the misconceptions experienced by students. Based on the explanation of the results of the discussion, it can be concluded that class XII MIA SMA Negeri 3 Tarakan in the 2019/2020 school year experienced misconceptions with an average percentage of 37.32%. The highest misconception was in item 19 regarding motion based on the connector place with a percentage of 60% and the lowest misconception was in item 10 regarding the nervous system function with a percentage of 22.96%.Keywords:  Misconception, CRI